2017
DOI: 10.3892/ol.2017.5827
|View full text |Cite
|
Sign up to set email alerts
|

High expression of EGFR predicts poor survival in patients with resected T3 stage gastric adenocarcinoma and promotes cancer cell survival

Abstract: Epidermal growth factor receptor (EGFR) is an essential regulator and biomarker of several types of cancer. However, the association between its expression and prognosis in patients with resected T3 stage gastric adenocarcinoma (RT3-GA) remains to be determined. In total, 683 patients with resectable T3-GA who underwent surgery were retrospectively included in the present study, and their immunohistochemical data for EGFR expression were collected. The associations between the patients' clinicopathologic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
(30 reference statements)
0
15
0
1
Order By: Relevance
“…Epidermal growth factor receptor (EGFR), a member of the ErbB family, is considered to be overexpressed in gastric cancer and play role in the development of tumourigenesis . Recent evidence shows that MICAL‐L1 mediates EGFR endocytosis, overexpression of MICAL‐L1 may lead to the accumulation of EGFR in the late endosomal compartment .…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR), a member of the ErbB family, is considered to be overexpressed in gastric cancer and play role in the development of tumourigenesis . Recent evidence shows that MICAL‐L1 mediates EGFR endocytosis, overexpression of MICAL‐L1 may lead to the accumulation of EGFR in the late endosomal compartment .…”
Section: Introductionmentioning
confidence: 99%
“…16,[20][21][22] Many products of protein-coding genes, such as CEA, HER2 and EGFR, have been investigated widely and function as diagnostic markers and therapeutic targets in the clinic. [23][24][25] Up to now, the early diagnosis and treatment of GC have been a global problem, and thus, we need a better understanding of the expression pattern of lncRNAs in GC cells. In view of the important cause of GC, we explored the expression patterns of lncRNAs in H. pylori-infected GC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, CTD-2218G20.2 was predicted to interact with 86 proteins (Pearson correlation coefficient, PCC > 0.3), some of which, including PSG4, PSG5, and PSG7, could also interact with cancer-related proteins, including KISS1, TIMP2, MMP11, IGFBP1, EGFR, and CDKN1C ( Figure 4A). Notably, KISS1, TIMP2, MMP11, IGFBP1, and EGFR have been reported to be involved in the metastasis of gastric cancer (Guan-Zhen et al, 2007;Kou et al, 2013;Wang et al, 2017;Wang et al, 2018;Sato et al, 2019). These results suggested that CTD-2218G20.2 might participate in the cancer progression via these cancer-related proteins.…”
Section: Discussionmentioning
confidence: 87%